Systematic Literature Review: Penerapan Model Problem Based Learning dengan Pendekatan CRT untuk Meningkatkan Hasil Belajar - Kuntum Khoiro Ummah; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Conventinal teaching methods result in students being less active in the learning process, leading to poor learning outcomes. There is a need for teaching methods that encourage students to activity solve problems related to daily life, thereby optimizing the learning process. This study aims to conduct a Systematic Literature Review (SLR) approach guided by PRISMA, selecting 18 relevant articles. The articles used were those indexed in SINTA, GARUDA, and Google Scholar. The tesults of the study indicate that the use of the Problem-Based Learning model, when integrated with the CRT approach, can encourage students to be active and solve problems related to issues encountered in daily life. These findings emphasize the importance of integrating culture into learning to enchance learning outcomes, help students understand the material more easily, and serve as a strategy for introducing local culture.